TREATMENT OF FREQUENTLY SICK CHILDREN WITH MIXED INFECTION - M.S. Savenkova; A.A. Afans'eva; V.S. Minasyan; S.I. Tyurkina ("Paediatrician" Publishers LLC, 2011)
The article presents information on treatment of children with frequent mixed infections (herpes-viral and intracellular). Examination of frequently sick children included combination of diagnostic methods (microbiological, serological) for the selection of combined therapy. Inosine pranobex (Isoprinosine) used as a part of complex treatment of mixed infection in frequently sick children favored to decrease of the duration of main clinical symptoms and to elimination of antibodies to infectious agents in respiratory tract or to decrease of their titre in most frequently sick children. Good therapeutic effect was detected in children with herpes viral infection. Key words: frequently sick children, respiratory infections, herpes virus, inosine pranobex, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 83-88)